ChemInform Abstract: Organocatalytic Cascade Reactions: Diversity‐Oriented Synthesis for the Construction of Hydroisoquinoline Scaffolds. Issue 40 (30th September 2014) - Gomez, Clarisa Villegas; Cruz, David Cruz; Mose, Rasmus; Joergensen, Karl Anker
Abstract An organocatalytic cascade reaction mediated trienamine [4 + 2]‐cycloaddition/nucleophilic ring‐closing sequence is developed.